DIGITAL MARKETING STRATEGY TO INCREASE THE NUMBER OF NEW STUDENTS - ALKAF, RADTRIA (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2024)
The role of digital marketing strategies is pivotal in enhancing the enrollment of new students. This study explores the impact and effectiveness of employing digital marketing techniques to augment the recruitment of new participants within educational institutions, specifically focusing on Pondok Pesantren Al-Manaar Batuhampar. Utilizing a descriptive qualitative method, the research delves into the various aspects and gains a deeper understanding of issues related to attracting prospective students. The findings reveal that digital marketing strategies significantly outperform traditional methods, offering advantages in time efficiency and cost savings.Keywords: Strategy, Digital, Marketing, School, Enrollment